Rancang Bangun Aplikasi Pembelajaran Paud Berbasis Web dengan Fitur Gamifikasi pada Kober Boafeo - Berchmans John Sado; Kristianus Jago Tute; Benediktus Yoseph Bhae (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2025)
Traditional learning methods in Early Childhood Education (PAUD), such as textbooks and blackboards, are still widely used and tend to be less engaging, resulting in passive and less motivated students. This study aims to design and develop a web-based learning application with gamification features for PAUD Desa Boafeo. The development process employed the waterfall method through stages of requirement analysis, system design, implementation, and testing. The application includes features such as counting, number recognition, and word spelling, enhanced with gamification elements to create a more interactive and enjoyable learning experience. Black box testing results indicate that all features function as intended. The findings conclude that the proposed application supports teachers in delivering materials effectively and contributes to improving students’ learning motivation and overall learning effectiveness.